Colombia - Expanding Services to Low-Income Areas Comparing Private and Public Water Utilities - Sotomayor, Maria Angelica (World Bank, Washington, DC, 2012)
Colombia is one of the most active Latin American countries in incorporating private sector participation (PSP) in managing water utilities. One of the community's main concerns is that reforms that treat water and sanitation services as an economic asset rather than as a social good and that allow providers to apply commercial (profit-oriented) criteria, may tend to restrict access to the services for low-income users, because they are not perceived as attractive business clients by private entrepreneurs. The government is embarking on a water sector modernization program whose strategy is to promote PSP in water utilities. One of its objectives is to expand and improve the provision of services to the poor, so it was considered necessary to find out if the common perception of the population and the concern of the community that the private sector focuses on providing good services to the wealthy and neglects the poor, is anchored in reality and consistent with the performance of privatized utilities in Colombia. A study was carried out during project preparation to test this perception against actual experience.